Exercise capacity assessed with the one-minute sit-to-stand test (1-min STST) is associated with echocardiographic findings in patients with heart failure with preserved ejection fraction (HFpEF). (4th February 2022) - Kronberger, C; Oeztuerk, B; Mousavi, R; Litschauer, B; Dachs, T; Rettl, R; Camuz-Ligios, L; Badr Eslam, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background Heart failure with preserved ejection fraction (HFpEF) is a major cause of cardiovascular morbidity and mortality (1). Non-invasive imaging, particularly echocardiography, plays a central role in the evaluation of HFpEF patients. Numerous prognostic markers for mortality have been identified in patients with HFpEF, including right ventricular tricuspid annular plane systolic excursion (TAPSE) and estimated systolic pulmonary artery pressure (ePASP) [(2) (3) (4)]. ePASP is calculated with Doppler measurement of peak tricuspid regurgitation velocity (TRV). Despite those markers, precise risk stratification remains challenging. Recently the one-minute sit-to-stand-test (1-min STST), a quick and objective test of functional capacity that can be potentially used for risk stratification, has attracted the interest of researchers. In this test, participants are encouraged to stand up and sit down from a chair as quickly and as many times as possible within one minute. The 1-min STST provides valuable information on the ability to perform daily life activities in HFpEF patients and adds to our options of diagnostic tests in HFpEF. Purpose The aim of this investigation was to prospectively examine whether 1-min STST results correlate with transthoracic echocardiographic parameters in a group of HFpEF patients. Patient and methods 32 HFpEF patients [59% New York Heart Association (NYHA) Class III, 63% female, age (mean ± standard deviation) 70 ± 11 years and 66% atrial fibrillation] were prospectively studied. Functional performance was examined with the 1-min STST. Echocardiographic estimations of pulmonary artery pressure and additional parameters (TRV and systolic function measured by echocardiography) as well as clinical characteristics were obtained. Results Mean 1-min STST repetitions were 16.41 ± 6.7. Twelve (38%) of the 32 HFpEF patients had moderate to severe mitral regurgitation and 29 (91%) had moderate or more tricuspid regurgitation. Mean left ventricular ejection fraction (LVEF) was 52.57 ± 1.74 % and mean ePASP was 65.81 ± 23.17 mmHg. 10 (32%) patients were in NYHA class I or II, 22 (69%) in NYHA class III or IV. There was a significant inverse association between higher NYHA class and the 1-min STST (t = 2.6, p = 0.012). The following additional parameters correlated significantly with the 1-min STST: ePASP (r = -0.545, p = 0.001), TRV (r = -0.598, p < 0.001) and the ratio of TAPSE/ePASP (r = 0.767, p = 0.001) (see table 1). Interestingly, the decline in oxygen saturation during the 1-min STST showed significant correlation with ePASP (r = -0.559, p < 0.001) and TRV (r = 0.540, p = 0.002). Conclusion Our investigation shows a direct linear correlation between ePASP, TRV and TAPSE/ePASP measured by echocardiography and measurements of functional capacity derived by the 1-min STST. Thus, the current results emphasize the role of the 1-min STST as an additional diagnostic tool in patients with HFpEF.